2020
DOI: 10.1002/jqs.3248
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pleistocene–Holocene climate shifts on vegetation and fire dynamics and its implications for Prearchaic humans in the central Great Basin, USA

Abstract: The effects of climate change during the Terminal Pleistocene-Early Holocene transition on ecosystems and early Prearchaic hunter-gatherers in the central Great Basin of North America are not well understood. We present a palynological reconstruction of regional vegetation and fire history in Grass Valley, central Nevada, from~14 to~7.5k cal a BP showing that Pinus-dominated woodlands were replaced by dry-adapted steppe and desert vegetation accompanied by an increase in regional fire activity at the beginning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Prior studies at high-elevation lakes in the eastern Sierra Nevada show that Early Holocene vegetation communities were open, wooded environments dominated by Pinus , Quercus , and shrubs, also suggesting dispersal upslope and stratification of vegetation previously found in Mono Basin (Anderson, 1990a; Davis, 1999a; MacDonald et al, 2008). Early Holocene dryness has been observed throughout the Sierra Nevada and Great Basin (Davis and Moratto, 1988; Anderson and Smith, 1994; Mensing, 2001; Brugger and Rhode, 2020), based on the decline in mesophilic arboreal taxa at lower elevations and the establishment of the semiarid vegetation assemblages seen today. Similarly, the complete absence of Sporormiella from 11,500–9,200 cal yr BP captures the final extirpation of Pleistocene megafauna in the basin, also consistent with the last appearance dates of megafauna fossils found in the Great Basin (Grayson, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies at high-elevation lakes in the eastern Sierra Nevada show that Early Holocene vegetation communities were open, wooded environments dominated by Pinus , Quercus , and shrubs, also suggesting dispersal upslope and stratification of vegetation previously found in Mono Basin (Anderson, 1990a; Davis, 1999a; MacDonald et al, 2008). Early Holocene dryness has been observed throughout the Sierra Nevada and Great Basin (Davis and Moratto, 1988; Anderson and Smith, 1994; Mensing, 2001; Brugger and Rhode, 2020), based on the decline in mesophilic arboreal taxa at lower elevations and the establishment of the semiarid vegetation assemblages seen today. Similarly, the complete absence of Sporormiella from 11,500–9,200 cal yr BP captures the final extirpation of Pleistocene megafauna in the basin, also consistent with the last appearance dates of megafauna fossils found in the Great Basin (Grayson, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work from the Great Basin has suggested that megafauna populations were low in comparison to the Mojave Desert to the south (Grayson, 2016). This appears to be reflected in limited Sporormiella presence in pollen studies from Great Basin wetlands (e.g., Gund Ranch; Brugger and Rhode, 2020). Yet, the high and relatively consistent presence of Sporormiella in Mono Lake sediments indicates higher megafauna activity, and implies that the rim of the Great Basin and Sierra Nevada may have provided more suitable habitats for megafauna than the central Great Basin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the eastern portion of this subregion is the Great Basin shrub steppe, where the few pollen records that exist are from high-elevation sites and low-elevation wetlands that are sensitive to fluctuating water tables, recorded as large fluctuations in Cyperaceae pollen. Increases in open-land cover taxa (Cyperaceae, Poaceae, Asteraceae) between 10-7.5 ka and after 3 ka in this region may reflect either local expansion of alpine meadows and wetlands or expansion of steppe more broadly (Mensing et al, 2008;Brugger and Rhode, 2020;Minckley et al, 2007;Thompson, 1992). Note, however, that desert, steppe, and other open-land arid ecosystems are likely to be underrepresented in these reconstructions, due to a scarcity of dryland sites.…”
Section: Pacific Coast Cascade and Sierra Nevada Ranges (Pccs)mentioning
confidence: 95%